TUBERCULOSIS IN CHILDREN IN THE RUSSIAN FEDERATION AT THE PRESENT STAGE - A. V. Mordyk; E. A. Tsygankova; L. V. Puzyryova; A. A. Turitsa (Union of pediatricians of Russia, 2014)
The literature review presents data on peculiarities of tuberculosis epidemiology, incidence rate and clinical pattern in children in the Russian Federation. Over the last 5 years, the age structure of the children developing tuberculosis has significantly changed: the share of children of small and preschool age increased, whereas the share of 7-14-year-old children decreased. Tuberculosis of thoracic lymph nodes predominates in the structure of clinical forms of tuberculosis of respiratory organs in children; small forms predominate, which indicates improvement of diagnostic capabilities. However, a rather large number of children with calcination stage of the tubercular process is observed. Further improvement of early detection of a tubercular infection is a powerful tool of preventing complicated and progressive forms of tuberculosis in children.